2012
DOI: 10.1089/ten.tec.2011.0490
|View full text |Cite
|
Sign up to set email alerts
|

A Fiber-Optic-Based Imaging System for Nondestructive Assessment of Cell-Seeded Tissue-Engineered Scaffolds

Abstract: A major limitation in tissue engineering is the lack of nondestructive methods that assess the development of tissue scaffolds undergoing preconditioning in bioreactors. Due to significant optical scattering in most scaffolding materials, current microscope-based imaging methods cannot ''see'' through thick and optically opaque tissue constructs. To address this deficiency, we developed a fiber-optic-based imaging method that is capable of nondestructive imaging of fluorescently labeled cells through a thick a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…microscopy). We recently published a study that demonstrated the development of a novel imaging system utilizing miniature fiber optical devices for nondestructive, single-cell-level resolution imaging of bioengineered tissue constructs [47,48]. The current study demonstrates the ability to positively identify implanted GFP-MPCs and -ECs after 8 weeks implantation in vivo , a sufficiently long enough time to follow many regenerative processes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…microscopy). We recently published a study that demonstrated the development of a novel imaging system utilizing miniature fiber optical devices for nondestructive, single-cell-level resolution imaging of bioengineered tissue constructs [47,48]. The current study demonstrates the ability to positively identify implanted GFP-MPCs and -ECs after 8 weeks implantation in vivo , a sufficiently long enough time to follow many regenerative processes.…”
Section: Discussionmentioning
confidence: 89%
“…Subsequently, we demonstrated the ability to image the interactions and differentiation capabilities of 3 fluorescently labeled cell types: MPCs, ECs and PCs, in real time in vitro , demonstrating a biological fluorescent imaging application. Combining the method developed here with the fiber-optic-based imaging modality described before [47,48], it will be possible to document tissue development and monitor the dynamic interplay between multiple cells types in vivo , in real-time, and with single-cell-level resolution. Such a technology may serve as a potent platform for testing the effects of different biological or pharmacological agents on tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are different technologies to obtain such information including multiphoton imaging [161]. Another approach is through the use of fiber opticbased imaging [162,163] that provides deeper penetration than any other imaging method and yields information that ranges from cell morphology to functional analysis, all in real time (Figure 3). There is a growing interest in making fluorescent proteins in the far red range that would improve imaging for in vivo application such as in the case of the new infrared fluorescent protein [164].…”
Section: Vascular Graft Assessmentmentioning
confidence: 99%
“…Optical imaging techniques, including multiphoton imaging [82], two photon and confocal microscopy, have the potential to monitor individual fluorescently labeled cells [83]; however, these techniques have a limited penetration depth, which limits their application in TEBV monitoring. Our laboratory has recently developed an optical fiber-based fluorescence imaging system ( Figure 3A) [84,85], which decouples the excitation from the optical fiber and the detection. This approach has the potential to achieve deeper penetration and longer working distance than standard microscopy; further, this technology yields real-time information regarding cell morphology and function and could be applied to both in vitro and in vivo systems Figure 3B-C.…”
Section: Tebv Assessmentmentioning
confidence: 99%